2013
DOI: 10.4085/1062-6050-48.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Spindle Traffic in Functionally Unstable Ankles During Ligamentous Stress

Abstract: Context: Ankle sprains are common in athletes, with functional ankle instability (FAI) developing in approximately half of cases. The relationship between laxity and FAI has been inconclusive, suggesting that instability may be caused by insufficient sensorimotor function and dynamic restraint. Research has suggested that deafferentation of peripheral mechanoreceptors potentially causes FAI; however, direct evidence confirming peripheral sensory deficits has been elusive because previous inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…However it is now known that joint proprioceptors provide input throughout a joint's entire ROM under both low and high load conditions stimulating strong discharges from the muscle spindle and are thus vital for joint stability (Sojka, Johansson et al 1989, Johansson, Lorentzon et al 1990, Needle, Charles et al 2013.…”
Section: Proprioceptorsmentioning
confidence: 98%
“…However it is now known that joint proprioceptors provide input throughout a joint's entire ROM under both low and high load conditions stimulating strong discharges from the muscle spindle and are thus vital for joint stability (Sojka, Johansson et al 1989, Johansson, Lorentzon et al 1990, Needle, Charles et al 2013.…”
Section: Proprioceptorsmentioning
confidence: 98%
“…The delayed muscle reaction times implied that neuromuscular control was altered by the damaged mechanoreceptors due to ligamentous injury. Tissue trauma from an ankle sprain may therefore decrease the amplitude of sensory traffic 17) . Khin Myo Hla et al 33) , conversely, theorized that irritability of mechanoreceptors and/or nociceptors in a limb that had undergone an ankle sprain, increased the amplitude of sensory traffic, possibly suppressing the activity of γ motor neurons in the peroneus muscles.…”
Section: Muscle Reaction Timementioning
confidence: 99%
“…Resultant tissue trauma from an ankle sprain could decrease the amplitude of sensory traffic (from capsuloligamentous and musculotendinous mechanoreceptors in the maintenance of joint sensation) at low levels of force. Unfortunately, the decrease in afferent traffic persisted in FAI individuals 16,17) . Palmieri-Smith et al 18) suggested that one of the plausible mechanisms leading to reduced peroneus muscle activity was the altered afferent traffic influencing the γ loop system.…”
Section: Introductionmentioning
confidence: 99%
“…38 Pietrosimone et al 39 concluded that alterations in neuromuscular function following a joint injury contribute to altered biomechanics possibly affecting long-term functional outcomes. Needle et al 40 suggest that subjective instability may be related to deficits in muscle spindle function during mechanical loading of the ankle. These studies provide support for the presence of neuromuscular dysfunction in CAI.…”
Section: Introductionmentioning
confidence: 98%